Challenges of Online Language and Literature Learning to the BSE-English Students of Pangasinan State University-Bayambang - Dela Cruz, Fariz Montemayor (IC-ITECHS, 2024)
This descriptive research aimed to identify challenges in online language and literature learning faced by Bachelor of Secondary Education - Major in English students at Pangasinan State University, Bayambang Campus, and to propose coping strategies. The study surveyed 153 students using a structured questionnaire with three sections: sociodemographic profile, challenges in online learning, and coping strategies. Data collection was facilitated online via Google Forms, and a non-experimental descriptive approach was applied to analyze the responses. Results indicated that most respondents were female, second-year students from low-income families (earning Php 10,000 or less monthly). The majority relied on mobile phones for online learning and expressed a preference for traditional, face-to-face classes. Key challenges impacting academic performance included difficulties in language and literature learning, self-regulation, technological literacy and competency, technological sufficiency, and learning environment—all rated as having a “Great Extent” effect on learning outcomes. The most effective coping strategies identified were self-discipline (79.1% of respondents), self-study (78.4%), and adaptation (73.2%). These strategies enabled students to navigate the demands of online learning. The study suggests further research to examine the relationship between student profiles and challenges in online education to deepen understanding of specific factors influencing academic experiences and outcomes.